Butch Bottom-Femme Top? An exploration of lesbian stereotypes - Walker, Ja’nina J.; Golub, Sarit A.; Bimbi, David S.; Parsons, Jeffrey T. (Journal of Lesbian Studies, 2012)
Lesbian gender labels (i.e., butch, soft butch, butch/femme, femme, and high femme) have set the stage for assumptions about lesbian attractions to sexual behaviors. This study explored the intersection of lesbian gender labels and attraction to sexual behaviors in 214 lesbian-identified women. Participants ranged in age from 18 to 69 with 48% being women of color. Contrary to stereotypes about sexual behavior in the lesbian community, very few differences emerged in regard to lesbian gender label. Overall, results do not support stereotypes about lesbian gender labels and suggest that behaviors in the lesbian community are fluid across labels.
Keywords: 2000 à aujourd'hui; 2000-2009; amériques; butch; identités LGBTQIA2+; personnes lesbiennes; périodes historiques; ressource en ligne; régions géographiques; états-unis